The influence of cellulose derivatives on water structure in gypsum. (30th January 2018) - Czaderna, Anna; Kocemba, Aleksandra; Kozanecki, Marcin; Mucha, Maria; Mróz, Patrycja
Highlights: Water structure in gypsum at different setting state was presented. Differences between surface and fracture of gypsum pastes were identified by FTIR. Cellulose derivatives modifiers retard the gypsum setting process. The model of supramolecular structure of gypsum with polymer addition was proposed. Abstract: In this study the influence of cellulose derivatives modifiers: 2-hydroxyethyl methylcellulose (HEMC), hydroxypropyl methylcellulose (HPMC) and hydroxypropyl cellulose (HPC) on the gypsum setting process and their respective changes in water arrangement were analysed. IR spectroscopy revealed the differences in the water structure between the surface and the fracture of gypsum samples. In comparison to pure gypsum, the setting process is slower in the presence of cellulose derivatives as the hydrophilic polymer partially traps the water molecules. Through the comparison of IR, SEM, DSC and micro-mechanical measurements supramolecular model of gypsum structure containing cellulose derivatives which stabilized water clusters was proposed.